A Case Study on the Corrosion of an Aging Jack-Up Drilling Rig - Roohollah Babaei-Mahani; Sirous Yasseri; Wayne Lam; Pouyan Talebizadehsardari (Journal of Marine Science and Engineering)
Corrosion costs the Oil & Gas Industry billions of pounds annually, primarily due to environmental factors such as high salinity, temperature fluctuations, and humidity in marine environments. Mobile Offshore Drilling Units (MODUs), especially jack-up rigs, are particularly susceptible to these dangers. This paper examines the impact of cold stacking on aging jack-up rigs and highlights how the absence of an adequate corrosion control system can accelerate structural deterioration. Our findings show that repair costs following cold stacking can far exceed the costs associated with maintaining rigs in a warm-stacked state. Preload tanks are critical areas prone to degradation due to microbiologically influenced corrosion (MIC) and inadequate preservation practices. Furthermore, although high-strength steels are frequently utilized in the construction of jack-up rigs due to their durability, we illustrate that, in the absence of meticulously devised preventative measures, these steels are susceptible to considerable corrosion, resulting in substantial repair expenses and diminished operational lifespans. This study highlights the significance of proactive corrosion control measures in maintaining the long-term structural integrity and cost-effectiveness of offshore drilling units.